The osteoporotic male: Overlooked and undermanaged? - Madeo, Bruno (Dove Medical Press, 2007)
Age-related bone loss in men is a poorly understood phenomenon, although increasing data on the pathophysiology of bone in men is becoming available. Most of what we know on bone pathophysiology derives from studies on women. The well-known association between menopause and osteoporosis is far from been disproven. However, male osteoporosis is a relatively new phenomenon. Its novelty is in part compensated for by the number of studies on female osteoporosis and bone pathophysiology. On the other hand, the deeper understanding of female osteoporosis could lead to an underestimation of this condition in the male counterpart. The longer life-span exposes a number of men to the risk of mild-to-severe hypogonadism which in turn we know to be one of the pathogenetic steps toward the loss of bone mineral content in men and in women. Hypogonadism might therefore be one among many corrigible risk factors such as cigarette smoking and alcohol abuse against which clinicians should act in order to prevent osteoporosis and its complications. Treatments with calcium plus vitamin D and bisphophonates are widely used in men, when osteoporosis is documented and hypogonadism has been excluded. The poor knowledge on male osteoporosis accounts for the lack of well shared protocols for the clinical management of the disease. This review focuses on the clinical approach and treatment strategy for osteoporosis in men with particular attention to its relationship with male hypogonadism.